IMPROVING THE PRACTICAL TRAINING OF FUTURE TEACHERS IN COLLABORATIVE LEARNING AS A PEDAGOGICAL PROBLEM (International journal of artificial intelligence, 2025)
This article explores the pedagogical problems associated with improving the practical training of future teachers within the framework of collaborative learning between KSU and YKSG. The main focus is on identifying barriers such as curriculum misalignment, differences in pedagogical standards, and coordination difficulties, as well as developing ways to overcome them. An experiment involving 90 students showed that joint practical modules contribute to a significant improvement in methodological and organizational skills. The results emphasize the need to unify educational approaches for effective intercultural training. The recommendations are aimed at integrating joint practices into curricula to improve the quality of pedagogical education.